Transcriptome of Endophyte-Positive and Endophyte-Free Tall Fescue Under Field Stresses - Islam, Md. Shofiqul; Krom, Nick; Kwon, Taegun; Li, Guifen; Saha, Malay C. (Frontiers in Plant Science, 2022)
Tall fescue (Festuca arundinacea Schreb.) is one of the primary sources of forage for livestock. It grows well in the marginal soils of the temperate zones. It hosts a fungal endophyte (Epichloë coenophiala), which helps the plants to tolerate abiotic and biotic stresses. The genomic and transcriptomic resources of tall fescue are very limited, due to a complex genetic background and outbreeding modes of pollination. The aim of this study was to identify differentially expressed genes (DEGs) in two tissues (pseudostem and leaf blade) between novel endophyte-positive (E+) and endophyte-free (E-) Texoma MaxQ II tall fescue genotypes. Samples were collected at three diurnal time points: morning (7:40-9:00 a.m.), afternoon (1:15-2:15 p.m.), and evening (4:45-5:45 p.m.) in the field environment. By exploring the transcriptional landscape via RNA-seq, for the first time, we generated 226,054 and 224,376 transcripts from E+ and E- tall fescue, respectively through de novo assembly. The upregulated transcripts were detected fewer than the downregulated ones in both tissues (S: 803 up and 878 down; L: 783 up and 846 down) under the freezing temperatures (-3.0 to 0.5°C) in the morning. Gene Ontology enrichment analysis identified 10 GO terms only in the morning samples. Metabolic pathway and biosynthesis of secondary metabolite genes showed lowest number of DEGs under morning freezing stress and highest number in evening cold (10 to 12°C) condition. The DEGs expressed under morning stress condition and, more importantly, the nine candidate genes identified under morning freezing temperatures, of which several are orthologs of rice phytochrome A, phytochrome C, and ethylene receptor genes, might be the possible route underlying cold tolerance in tall fescue.